Effect of feeding management of broodstock on breeding performance of bata (Labeo bata) (Asian Journal of Medical and Biological Research, 2016)
Labeo bata is one of the important minor carps in Bangladesh with great demand as good table fish. The study was conducted to observe the breeding performance at different management practices in Mafatema, Rupali, Modhumoti and Anan fish hatchery and disinfection treatments of water, eggs and fry in Jessore, Bangladesh during 10 March 2014 to 15 May 2015. An improvement in broodstock nutrition and feeding has been shown to greatly improve seed production. Protein and lipid percentage of broodstock diet have been identified as major dietary factors. Protein level was 24.77%, 23.47%, 18.08%, 17.78% and lipid level was 11.07%, 9.50%, 7.74%, 8.14% in Mafatema, Rupali, Modhumoti and Anan fish hatchery respectively. Three concentrations of four chemical-formalin (10, 20, 30 mg/L), malachite green (1, 3, 5 mg/L), NaCl (1, 2, 3 g/L) and methylene blue ( 1, 3, 5 mg/L) treatment regimes and a control were compared for efficacy in treating L. bata eggs to prevent fungus and bacterial infection and improve hatch and survival rate of fry. Highest correlation value between absolute fecundity and body weight (r=.938, p